2014
DOI: 10.1590/1678-4499.0136
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and agronomic traits in soybean according to crop rotation systems

Abstract: The effects of crop rotation systems (CRS) on soybean yield and agronomic characteristics were evaluated from 1996/1997 to 2010/2011 at Embrapa Trigo, Passo Fundo (RS), Brazil. Four soil management systems (SMS) were compared, namely: 1) no tillage, 2) minimum tillage, 3) conventional tillage using a disk plow and a disk harrow, and 4) conventional using a moldboard and a disk harrow -and three CRS: system I (wheat/soybean), system II (wheat/soybean and common vetch/corn or sorghum) and system III (wheat/soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
1
9
1
3
Order By: Relevance
“…Broad base ridges of 15.0 and 22.5 m were placed at the intermediate position, while surface drainage was inferior to the other treatments. These results are inferior to those observed by Santos et al (2014), who found mean values of plant height of 86 cm over 14 growing seasons. Again, there is the occurrence of damage resulting from precipitations below the climatological normal in the 2014/2015 season.…”
Section: Resultscontrasting
confidence: 98%
“…Broad base ridges of 15.0 and 22.5 m were placed at the intermediate position, while surface drainage was inferior to the other treatments. These results are inferior to those observed by Santos et al (2014), who found mean values of plant height of 86 cm over 14 growing seasons. Again, there is the occurrence of damage resulting from precipitations below the climatological normal in the 2014/2015 season.…”
Section: Resultscontrasting
confidence: 98%
“…In general, soybean in rotation with cereals results in higher yields than monoculture soybean (Santos et al, 2014;Stanger et al, 2008). This study showed that average soybean yields were higher in C-C-S than in C-S in the majority of locations (Table 5).…”
Section: Rotation Effect On Soybean Yield and Economic Returnmentioning
confidence: 70%
“…In the studies by Santos et al (2014), in area with coverage plants, no difference was observed in the soybean grain yield during the period when the study was carried out, 1996/1997 to 2010/2011. Santos et al (2013), found no significant difference between coverage plants, as for the grain yield, however, after the vetch crop, the soybeans that were planted obtained the highest number of pods, number of grains and grain mass per plant than those that were sown in the other systems.…”
Section: Microbiological Soil Properties and Soybean Yieldmentioning
confidence: 91%